Influence of natural organic matter and pH on phosphate removal by and filterable lanthanum release from lanthanum-modified bentonite. (1st September 2021) - Zhi, Yue; Call, Douglas F.; Grieger, Khara D.; Duckworth, Owen W.; Jones, Jacob L.; Knappe, Detlef R.U.
Highlights: Natural organic matter (NOM) adversely impacted phosphate removal. Impact of NOM on phosphate removal was pH-dependent. PO4 removal by lanthanum-modified bentonite decreased by 11–25% under the highest NOM loading. NOM increased release of filterable lanthanum from lanthanum-modified bentonite. Abstract: Lanthanum modified bentonite (LMB) has been applied to eutrophic lakes to reduce phosphorus (P) concentrations in the water column and mitigate P release from sediments. Previous experiments suggest that natural organic matter (NOM) can interfere with phosphate (PO4 )-binding to LMB and exacerbate lanthanum (La)-release from bentonite. This evidence served as motivation for this study to systematically determine the effects of NOM, solution pH, and bentonite as a La carrier on P removal. We conducted both geochemical modeling and controlled-laboratory batch kinetic experiments to understand the pH-dependent impacts of humic and fulvic acids on PO4 -binding to LMB and La release from LMB. The role of bentonite was studied by comparing PO4 removal obtained by LMB and La 3+ (added as LaCl3 salt to represent the La-containing component of LMB). Our results from both geochemical modeling and batch experiments indicate that the PO4 -binding ability of LMB is decreased in the presence of NOM, and the decrease is more pronounced at pH 8.5 than at 6. At the highest evaluated NOM concentration (28 mg C L −1 ), PO4 -removal by La 3+ was substantially lower than that by LMB, implying that bentonite clay in LMB shielded La from interactions with NOM, while still allowing PO4 capture by La. Finally, the presence of NOM promoted La-release from LMB, and the amount of La released depended on solution pH and both the type (i.e., fulvic/humic acid ratio) and concentration of NOM. Overall, these results provide an important basis for management of P in lakes and eutrophication control that relies on LMB applications. Graphical abstract: Image, graphical abstract